Antifungal activity of chitosan and its combination with the yeast Debaryomyces hansenii F9D for the control of Penicillium expansum in apples and pears stored at low temperatures. Issue 4 (2nd October 2022) - Arrarte, Eloisa; Zaccari, Fernanda; Garmendia, Gabriela; Castiglioni, Jorge; Vero, Silvana
Abstract: Penicillium expansum is an important pathogen of cold-stored fruit, currently controlled by chemical fungicides. In this work chitosan combined with the biocontrol yeast Debaryomyces hansenii F9D was tested as a safer alternative for its control on cold-stored apples and pears. When medium molecular weight chitosan was applied on fruit a reduction of rot incidence of 62% and 53% was achieved in apples and pears. respectively. When chitosan was combined with the yeast, disease reduction was 76% and 90%. The combination of biological control with chitosan appears as a feasible strategy for the control of phytopathogenic fungi.